Modul Elektronik Berbasis Pendekatan Saintifik pada Materi Ikatan Kimia - Putri Milenia Hutabarat; Aulia Sanova; Syamsurizal Syamsurizal (Chemistry Education Department of Education and Teaching Faculty, 2021)
The role of technology in education is at the forefront of developing innovative teaching materials that may facilitate students' learning needs. The purpose of this research was to determine the procedure for developing an electronic module based on a scientific approach for the chemical bonding topic, as well as to determine whether the developed media is theoretically and practically feasible. This electronic module was designed with students with visual learning styles in mind, and the topics are presented in a scientific manner. The methods were implemented using the Lee and Owens model, which required several steps such as analysis, design, development, implementation, and evaluation. The results showed that the electronic module was deemed feasible as a digital teaching material by expert judges. Based on practitioner testing during the learning process, this module was effective as a teaching material, as evidenced by 89.28 percent (